Characterization of the electrically evoked release of substance P from dorsal root ganglion neurons: methods and dihydropyridine sensitivity - Holz, GG (J Neurosci, 1988)
The mechanism by which dihydropyridines (DHPs) modulate the electrically evoked or KCI-induced release of substance P (SP) from embryonic chick dorsal root ganglion (DRG) neurons was investigated in the present study. The release of SP, as measured by radioimmunoassay (RIA), was characterized in terms of its dependence on extracellular calcium ion, its stimulus-response relationship, its sensitivity to the calcium-channel blocker omega conus toxin (omega-CgTx), and its modulation by the DHPs Bay K 8644 and nifedipine. Here it is reported that omega-CgTx (1 microM) blocked the electrically evoked release of SP. In contrast, the calcium-channel agonist Bay K 8644 (5 microM) facilitated the release of SP (by 45%), whereas the calcium-channel antagonist nifedipine (5 microM) was without effect. When the release of SP was triggered by depolarization of cultures with 60 mM KCI, the actions of the DHPs became much more pronounced. Under these conditions, Bay K 8644 facilitated (by 115%), whereas nifedipine inhibited (by 58%), peptide secretion. Voltage-clamp analysis of DRG cell calcium currents demonstrated that these actions of omega-CgTx, Bay K 8644, and nifedipine are explicable in terms of their effects on the slowly inactivating (L-type) calcium current. On the basis of these findings, it is suggested that the SP release mechanism exhibits DHP sensitivity due to the involvement of L-type calcium channels in the neurosecretory process. This model predicts that the voltage and time- dependent antagonist actions of nifedipine are sufficient to explain its failure to inhibit the electrically evoked release of SP.